Organic‐walled microfossils from the Kistedalen Formation, Norway: acritarch chronostratigraphy of the Baltic Miaolingian and evolutionary trends of placoid acritarchs. (26th August 2022) - Palacios, Teodoro; Högström, Anette E. S.; Jensen, Sören; Ebbestad, Jan Ove R.; Agić, Heda; Høyberget, Magne; Meinhold, Guido; Taylor, Wendy L.
Abstract: New acritarch data from the Kistedalen Formation based on two sections with continuous exposure enable us to establish the most detailed Miaolingian acritarch biozonation in Baltica to date. Six interval zones previously established in Gondwana, the Eliasum llaniscum, Cristallinium cambriense, Adara alea, Timofeevia lancarae, Cristallinium dubium and Vulcanisphaera turbata zones, are identified, and their correlations within the Acado‐Baltic Province examined. The diagnoses of Retisphaeridium, Cristallinium, Retisphaeridium dichamerum, Retisphaeridium lechistanium, Cristallinium dubium and Cristallinium cambriense are emended and the new species Retisphaeridium rugulatum sp. nov. and Retisphaeridium minimum sp. nov. are described. The diagnosis of Retisphaeridium ovillense (Cramer & Díez) Vanguestaine is emended and the species assigned to Dictyotidium ovillense comb. nov. The main evolutionary changes of the placoid acritarchs during the Miaolingian are analysed. Comparison with previous acritarch data from the Kistedalen Formation suggests that different extraction methodologies may result in significant bias in the recovered fossil record.